Musicografia braille: Estratégias e recursos para a formação musical da pessoa normovisual, cega e/ou com deficiência visual - Malheiros, Ozani Pereira de Oliveira (2017)
In the Special and Inclusive Basic Education, research and teaching have been more explored than in the area of Musical Education, especially in what concerns the teaching of blind and/or visually impaired people, where most of them learn an instrument in an informal way or “by ear”. As the writing for musical writing and other areas of teaching/learning of this specific audience is unique and totally different from the others, few educators and researchers are willing to follow these new (old) ways, throughout their teaching journey. Therefore, this study, entitled: Musicography Braille: strategies and resources for the musical training of blind and/or visually impaired people, is the result of anxieties in the course of experiences with this target public, which led to the following guiding question: What strategies and resources can help support the teaching of Braille Musicography to non-blind people, blind people and/or people with low vision? Since this is a qualitative research, it has as methodology the action research, because it presents a process that is based on a cycle, where it allows the intervention of the researcher in the process of the action, seeking the improvement of the practice. In this way, the research had as general objective: to investigate strategies and methodological resources for the teaching of Braille Musicography to normovisual, blind and/or visually impaired students. The specific objectives were: to work the intersection of musical realities of normovisual learners, educating the blind and/or with low eyesight, in the classroom; identify tools that enable the improvement of Braille Musicography learning; analyze the development of these students during this study and transcribe, from Braille paint, the result of this research. For this, 14 classes were taught, including filming, photographing and testimonials that were used as data collection. Changes in the programmatic content occurred during action, aiming to meet the needs of the students. In this way, I concluded that the work of raising awareness among the students, the materials and the strategies used for the teaching/learning of Braille Musicography in an inclusive context is possible and fundamental. It also enables us to reflect on the musical education of the blind child, in the same way that one thinks of the musical education of normovisual children, in case they choose to follow the academic life as a musician.